Which shape fits best? Designing the organizational form of local government procurement. Issue 3 (June 2019) - Patrucco, Andrea Stefano; Walker, Helen; Luzzini, Davide; Ronchi, Stefano
Abstract: The way that public procurement activities are organized has an impact on the performance of public institutions. By reviewing the literature on public procurement organization dimensions this study offers a conceptual framework for public procurement organizational design, distinguishing between the macro, micro and process level dimensions. The framework is tested across the procurement departments of 15 local governments in Wales and Italy. We identify six alternative organizational configurations, differing in their level of centralization and their procurement status within the institution. Their suitability and potential for redesign depend on several internal and external contextual factors (goals, government decision, regulation, geographical environment) in line with the contingency view of organizational design. Highlights: We build a theoretical framework for analyzing contingent factors and organizational dimensions of public procurement. We analyzed local government organizations in Italy and UK. We identify six potential configurations for procurement department in local government, providing their description and suitability according to contextual variables.